I. Yusupov's Anthropology of Philosophy - Orazbaev , Arislanbay (Indonesian Journal Publisher, 2024)
In this article, the works of the great poet of the Karakalpak people, the poetry star I. Yusupov, analyze the problem of man, the attitude of man to the world, his environment, ways and methods of self-improvement from a philosophical and anthropological point of view.